2023
DOI: 10.1007/s43621-023-00129-7
|View full text |Cite
|
Sign up to set email alerts
|

Perception of climate change in an academic community in Colombia—a pilot study in a developing country

Abstract: The study applied a climate change (CC) perception survey in Colombia between 2021 and 2022 to gather information about the national academic community from UNAD University (Universidad Nacional Abierta y a Distancia). The survey's fundamental component was the use of Yale's Six Americas Super Short Survey (SASSY) questions and algorithm, which allows the segmentation of the population into six audiences based on their views on climate change. In addition, the study analyzed the perception regarding causes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…The results offer important new insights into researchers' perceptions of the climate crisis across numerous measures as they explore data that has not previously been collected. When compared to researchers and academics in France and Colombia [55,56] and university students globally [50], we found that UK researchers' level of climate worry (94.8%) is similar. However, it is higher than the UK public (83%) [83] and even more so when accounting only for those who are extremely or very worried (73.6% compared to 46% general public) [84].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The results offer important new insights into researchers' perceptions of the climate crisis across numerous measures as they explore data that has not previously been collected. When compared to researchers and academics in France and Colombia [55,56] and university students globally [50], we found that UK researchers' level of climate worry (94.8%) is similar. However, it is higher than the UK public (83%) [83] and even more so when accounting only for those who are extremely or very worried (73.6% compared to 46% general public) [84].…”
Section: Discussionmentioning
confidence: 82%
“…There is some support for climate action or greater sustainability in their job roles [52,54] but also a lack of professional development to do so [49]. Surveys of researchers across France and academics at a Colombian university found almost universal levels of concern about the climate crisis [55,56], yet in France this is not translating into corresponding action [54]. Barriers to conducting sustainability research include a lack of power, funding, motivation and a common goal [57][58][59], while lack of knowledge is a key barrier to reducing personal carbon emissions and taking climate action [49,60].…”
Section: Plos Climatementioning
confidence: 99%